Mutational Analysis of the Carboxy-Terminal (YGX)(4) Repeat Domain of CpsD, an Autophosphorylating Tyrosine Kinase Required for Capsule Biosynthesis in Streptococcus pneumoniae - Morona, Judy K. (American Society for Microbiology, 2003)
In Streptococcus pneumoniae, CpsB, CpsC, and CpsD are essential for encapsulation, and mutants containing deletions of cpsB, cpsC, or cpsD exhibit rough colony morphologies. CpsD is an autophosphorylating protein-tyrosine kinase, CpsC is required for CpsD tyrosine phosphorylation, and CpsB is a phosphotyrosine-protein phosphatase. We have previously shown that autophosphorylation of CpsD at tyrosine attenuates its activity and consequently reduces the level of encapsulation and negatively regulates CPS production. In this study, we further investigated the role of the carboxy-terminal (YGX)(4) repeat domain of CpsD in encapsulation. A CpsD truncation mutant in which the entire (YGX)(4) repeat domain was removed was indistinguishable from a strain in which the entire cpsD gene had been deleted, indicating that the carboxy-terminal (YGX)(4) tail is required for CpsD activity in capsular polysaccharide production. Double mutants having a single tyrosine residue at position 2, 3, or 4 in the (YGX)(4) repeat domain and lacking CpsB exhibited a rough colony morphology, indicating that in the absence of an active protein-tyrosine phosphatase, phosphorylation of just one of the tyrosine residues in the (YGX)(4) repeat was sufficient to inactivate CpsD. When various mutants in which CpsD had either one or combinations of two or three tyrosine residues in the (YGX)(4) repeat domain were examined, only those with three tyrosine residues in the (YGX)(4) repeat domain were indistinguishable from the wild-type strain. The mutants with either one or two tyrosine residues exhibited mucoid colony morphologies. Further analysis of the mucoid strains indicated that the mucoid phenotype was not due to overproduction of capsular polysaccharide, as these strains actually produced less capsular polysaccharide than the wild-type strain. Thus, the tyrosine residues in the (YGX)(4) repeat domain are essential for normal functioning of CpsD.